THE ROLE OF GREEN ECONOMY AS A DRIVER OF SUSTAINABLE BUSINESS - Andi Lisa Aryani Hamjan; M. Amir HM; Hukmiah Husain; Sitti Nikmah Marzuki (Jurnal Ilmiah Al-Tsarwah, 2025)
This study aims to examine the application of the green economy concept within the framework of sustainable business in Indonesia, focusing on the integration of economic, social, and environmental sustainability principles. It explores how the green economy can serve as a strategic foundation for ethical, inclusive, and environmentally responsible business transformation aligned with sustainable development goals. This study employs a literature review method by analyzing a wide range of academic sources, government policies, and international frameworks related to the green economy and sustainable business practices. Findings reveal that implementing green economy principles contributes to economic growth, while embedding ethical values, social responsibility, and resource efficiency as core foundations of modern business practices. Such integration enhances corporate competitiveness, strengthens reputation, and promotes social welfare through green innovation and sustainable employment creation. Furthermore, Islamic ethics reinforce these practices by promoting fairness, stewardship, and accountability in business operations. The study concludes that the green economy provides a strategic pathway for ethical and sustainable business transformation in Indonesia. Integrating Islamic ethical and spiritual values bridges theory and practice, fostering balanced economic growth, environmental preservation, and social welfare aligned with the triple bottom line of profit, planet, and people.